Optimize adaptive media playout using dynamic fuzzy logic control for video streaming - Abdul Khalib, Zahereel Ishwar; Ehtiba, Farij Omar; Ahmad, R. Badlishah; Salim, Naseer Sabri; Rahman, Mostafijur; Li, Mingfu (Multimedia tools and applications, 2018)
Adaptive Media Playout (AMP) controls adapt playout rate to prevent buffer outage and to reduce delay in playout. Most AMP techniques use buffer fullness or its variation as indicator to adapt to playout rate. Nonetheless, selecting a convenient buffer threshold of particular design is a great challenge. Based on this principle, Dynamic Fuzzy Logic (DFL) controls principle fused with AMP technique to propose a new technique, known as DFLAMP. The technique is implemented to reduce playout delay and prevent buffer outage. Moreover, DFLAMP is also utilized to adjust playout rate based on arrival rate variation and adapt playout rate to keep the buffer fullness around the desired level. Simulation results have indicated that DFLAMP technique efficiently outperforms other AMP approaches. DFLAMP shows 14.5% less buffer underflow, 25% less buffer overflow, and 26.4% less distortion of variance as compared to APTA. Moreover, it depicts 7.5% decreased total playout delay as compared to DPTA-APTA.